PENERAPAN TERAPI GUIDED IMAGERY TERHADAP PENURUNAN KECEMASAN DAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI - Lestari, Puspita Hanggit; Oktavia, Cristina; Ekasari, Mia Fatma; Ayu Pertiwi, Nur Fitri; Silviani, Nadhia Elsa (NHM PRESS, 2024)
Background: Hypertension is still a health problem that often occurs in the elderly. One of the factors that causes blood pressure to increase is anxiety. Anxiety can be reduced through the application of Guided imagery therapy. Guided imagery is a relaxation technique that relaxes the elderly and helps lower blood pressure. Method: The research used a case study method involving 3 elderly people. Application is carried out for 7 consecutive days with a duration of 15-20 minutes. Anxiety was measured using the HARS questionnaire. Results: The three elderly experienced a change in anxiety level with the result that 2 elderly people had a severe level of anxiety to a moderate level of anxiety and 1 elderly person went from a moderate level of anxiety to a mild level of anxiety. The three elderly also experienced changes in blood pressure with the results, The first elderly with previous blood pressure of 175/98 mmHg became 149/95 mmHg; The second elderly from previously 134/90 mmHg to 114/85 mmHg; and the 3rd elderly with previous blood pressure of 150/83 mmHg to 121/82 mmHg. Conclusion: Guided Imagery Therapy has an influence in reducing anxiety levels and blood pressure in hypertensive elderly.